Definition of the influence of obtaining method on physical and chemical characteristics of Ni (OH)2 powders - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2019)
Four types of hydroxide were chosen for the study. Two of them were synthesized using the industrial method and are used in alkaline batteries. The other two nickel hydroxide powders were synthesized according to the method described in modern literature. The first hydroxide was synthesized using the hydrolytic method from a solution of nickel salt and urea. The other was synthesized from a solution containing a mixture of nickel and aluminum salts in a 4:1 ratio and was precipitated with a solution of alkali. As a result, all chosen hydroxide powders differ in physico-chemical parameters: structure, phase composition, morphology. Thus, it was revealed that the synthesis method of nickel hydroxide, and in turn, differences in structure and morphology, have a significant impact on electrochemical and other physico-chemical properties of powders. As a result of measuring specific surface area using the dye absorption method, the measured values of the studied hydroxide were found to be 2.52 m2/g to 15.44 m2/g. The measured values were used to calculate diffusion coefficients. The diffusion coefficients were calculated for both anodic and cathodic processes, along with their averaged values. The obtained values of proton diffusion coefficients varied from 9.86∙10-15 to 9.87∙10-17 cm2/s. Comparison and analysis of electrochemical characteristics, specific surface area values and diffusion coefficients allowed making recommendations for hydroxide application. A mechanism was proposed, that explains the values of specific parameters, and the relation between the structure, synthesis method and physico-chemical parameters was revealed